2022
DOI: 10.1111/clr.13886
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported outcome measures comparing static computer‐aided implant surgery and conventional implant surgery for single‐tooth replacement: A randomized controlled trial

Abstract: Objective: To compare static computer-aided implant surgery (s-CAIS) and conventional implant surgery (CIS) for single-tooth replacement in posterior sites in terms of patient-reported outcome measures (PROMs).Methods: Forty patients were divided into two groups for treatment with s-CAIS (Test) and CIS (Control). Patients' anxiety level was measured using the modified dental anxiety score before implant surgery. After surgery, patients completed two questionnaires for 7 days. The first questionnaire assessed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 36 publications
(32 reference statements)
0
19
0
Order By: Relevance
“…Sancho‐Puchades et al 43 suggested some influence of a “novelty effect” of CAIS on patients' presurgical expectations, as they found that the majority of patients favored the CAIS approach even without having prior experience of implant surgery (CAIS preferred by 83% vs conventional by 6% of patients). However, when a more detailed assessment of presurgical expectations was conducted by Engkawong et al 8 (ie, anticipated symptoms duration and intensity) and Kunavisarut et al 9 (ie, Modified Dental Anxiety Score), no statistically significant differences were found between the expectations of patients scheduled for CAIS or conventional implant placement.…”
Section: Methodsmentioning
confidence: 98%
See 4 more Smart Citations
“…Sancho‐Puchades et al 43 suggested some influence of a “novelty effect” of CAIS on patients' presurgical expectations, as they found that the majority of patients favored the CAIS approach even without having prior experience of implant surgery (CAIS preferred by 83% vs conventional by 6% of patients). However, when a more detailed assessment of presurgical expectations was conducted by Engkawong et al 8 (ie, anticipated symptoms duration and intensity) and Kunavisarut et al 9 (ie, Modified Dental Anxiety Score), no statistically significant differences were found between the expectations of patients scheduled for CAIS or conventional implant placement.…”
Section: Methodsmentioning
confidence: 98%
“…Five RCTs and one small case‐control study reported short‐term postoperative PROs/PRE adequately for collective analysis. Three RCTs 8,9,43 utilized a VAS of 1‐10 to record pain and swelling among other outcomes but did not find any statistically significant difference in any major postoperative PROs. A small case‐control study (n = 24/41 implants) assessing the same outcomes did not attempt statistical analysis 16 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations